Bleomycin in verrucous squamous cell carcinoma of the oesophagus. - Sakurai, T. (BMJ Group, 1983)
A case of verrucous squamous cell carcinoma of the oesophagus treated with bleomycin is reported. Bleomycin brought prompt reduction of the tumour and relief of symptoms. There have been no previous reports on experience with anti-cancer agents for verrucous carcinoma of the oesophagus. Administration of bleomycin might be an effective treatment for verrucous carcinoma of the oesophagus.